Identifikasi Senyawa Flavonoid dan Aktivitas Antioksidan Ekstrak Etanol Buah Dewandaru (Eugenia uniflora L.) - Santoso, Puguh; Megawati, Fitria; Cintya Purnama Sari, Ni Wayan; Linda Paramita, Ni Kadek (Usadha, 2022)
Indonesia is a country with abundant natural wealth. Almost all kinds of plants can grow in this country. Most have been used since ancient times to treat various diseases. One of the efficacious plants used as medicine is the Dewandaru fruit (Eugenia uniflora L.). This study aims to identify the presence of flavonoid compounds in the Dewandaru fruit (Eugenia uniflora L.) and test the in vitro activity of the ethanol extract of the Dewandaru fruit. Dewandaru fruit extract (Eugenia uniflora L.) was prepared using the maceration extraction method with 96% ethanol solvent. The extraction process was carried out three times. The extract obtained was concentrated in a rotary evaporator at 40-45 °C and then dried in an oven at 40°C. The extracts obtained were identified by means of ultraviolet visible spectrophotometry thin-layer chromatography. obtained showed a positive reaction in the pre-test of flavonoids seen from the separation of red and from the separation of orange stains on thin-layer chromatography. The results of the in vitro test for the antioxidant activity of the ethanol extract of Dewandaru fruit showed an IC50 activity of 53.44 ppm.